Is the prevalence of asthma and related symptoms among Brazilian children related to socioeconomic status? - Solé, Dirceu; Camelo-Nunes, Inês Cristina; Wandalsen, Gustavo F.; Mallozi, Márcia C.; Naspitz, Charles K.; Cardoso, Maria Socorro; Barreto, Bruno A. Paes; Dantas, Vera; Britto, Murilo; Silva, Almerinda R.; Sarinho, Emanuel S. Cavalcanti; Soares, Francisco J. Passos; et al. (Taylor & Francis, 2008)
Objective. To evaluate the relationship between socioeconomic status (SES) and the prevalence of asthma and related symptoms among Brazilian children. Methods. The International Study of Asthma and Allergies in Childhood (ISAAC) written questionnaire was applied to 23,457 six- to seven- year-old schoolchildren (SC) and 58,144 thirteen- to fourteen-year-old adolescents (AD) from 20 Brazilian cities. SES was evaluated by infant mortality index, poverty index, and average nominal income for people older than 10 years of age. Results. Current asthma ranged from 16.5% to 31.2% among SC and from 11.8% to 30.5% among AD and severe asthma from 2.9% to 8.5% (SC) and 2.6% to 9.1% (AD). Higher values were observed in Brazilian-Northern, -Northeastern and -Southeastern centers. No significant association between SES and prevalence of asthma and related symptoms was observed. Conclusions. In Brazil, the prevalence of asthma and related symptoms is quite variable and independent of SES. Copyright © 2008 Informa Healthcare USA, Inc.
Keywords: Asthma; Children; Epidemiology; ISAAC; Prevalence; Wheezing; adolescent; age distribution; asthma; Brazil; child; controlled study; coughing; female; groups by age; human; income; infant mortality; major clinical study; male; poverty; prevalence; questionnaire; sleep disorder; social status; speech disorder; symptom; variance; wheezing; Adolescent; Child; Humans; Questionnaires; Socioeconomic Factors